Automated Network Management Systems / Current and Future Capabilities - Comer, Douglas E. (Pearson - Prentice Hall, 2007)
The writer identifies the properties of a comprehensive automated management system. Preface, The Network Management Challenge, Basics and Definitions, Configuration and Operation, Fault and Correction, Accounting and Billing, Security, Tools and Platforms, Management Tools and Technologies, Flow Data and Flow Analysis (NetFlow), Management Scripting, The future of Network Management, Architectures for Network Management Software, Design Tradeoffs, Open Questions and Research Problems, Bibliography, Index.